Influence of calcium additions on the compressive strength and microstructure of alkali-activated ceramic sanitary-ware - Reig, Lucía; Soriano, Lourdes; Tashima, Mauro M. [UNESP]; Borrachero, María V.; Monzó, Jose; Payá, Jordi (Wiley, 2018)
The ceramic sanitary-ware market generates large amounts of waste, both during the production process and due to construction and demolition practices. In this paper, the effect of different amounts and calcium sources (calcium hydroxide Ca(OH)2, calcium aluminate cement CAC, Portland cement PC) on the alkaline activation of ceramic sanitary-ware waste (CSW) was assessed. Blended samples were activated with NaOH and sodium silicate solutions and cured for 3 and 7 days at 65°C. The maximum amount of calcium source-type added to the system varied according to its influence on the compactability of the mortars.CSW was physico-chemically characterized and the compressive strength development of activated samples was assessed on the mortars. The nature of the reaction products was analyzed in pastes, by X-ray diffraction, thermogravimetric analysis, infrared spectroscopy and microscopic studies. The results show a great positive influence with the addition of moderate amounts of Ca(OH)2, PC and CAC on the mechanical properties. Among the typical hydrates usually observed in plain water-hydrated PC or CAC, only AH3 and a small amount of C3AH6 were identified in the alkali-activated CSW/CAC blended pastes, which indicates that Al and Ca from PC, CAC and Ca(OH)2 are taken up in the newly formed (N,C)-A-S-H or C-A-S-H gels.
Keywords: alkali activation; cements; geopolymers; mechanical properties; microstructure